2009
DOI: 10.5483/bmbrep.2009.42.10.691
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of pref-1 by E2F1 in 3T3 L1 cells

Abstract: The E2F gene family appears to regulate the proliferation and differentiation of events that are required for adipogenesis. Pref-1 is a transmembrane protein that inhibits adipocyte differentiation in 3T3-L1 cells. In this study, we found that the expression of pref-1 is regulated by the transcription factor E2F1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Because Trim28 is not a DNA-binding protein, we would like to know which protein recruits it to Dlk1 promoter. Previous studies indicated that Trim28 associated with E2f1 and E2f1 bound to Dlk1 promoter [ 34 , 35 ]. Knockdown of E2f1 attenuated Dlk1 expression and increased Pparg expression at treated with FDMI for two days ( Figure 7 a).…”
Section: Resultsmentioning
confidence: 99%
“…Because Trim28 is not a DNA-binding protein, we would like to know which protein recruits it to Dlk1 promoter. Previous studies indicated that Trim28 associated with E2f1 and E2f1 bound to Dlk1 promoter [ 34 , 35 ]. Knockdown of E2f1 attenuated Dlk1 expression and increased Pparg expression at treated with FDMI for two days ( Figure 7 a).…”
Section: Resultsmentioning
confidence: 99%
“…Further work revealed that ALY/REF binds to intronless transcripts too, via a different, splicing-independent, mechanism (Taniguchi and Ohno, 2008). Other examples include the export-associated THO complex which associates with spliced mRNAs but not with unspliced ones (Masuda et al, 2005), and the UAP56 splicing factor which also has a key role in export (Shen, 2009). …”
Section: Functions Associated With Ejc-harboring Transcriptsmentioning
confidence: 99%
“…Um estudo conduzido por SHEN et al (2009), demonstrou que o aumento da expressão de E2F1, um membro da família de fatores de transcrição denominados E2F, resulta na redução da expressão de DLK 1. De modo complementar, estudos em tecido adiposo revelam que, E2F1 induz a expressão de PPARγ e de C/EBPα, favorecendo desta forma o processo de adipogênese (Venugopal et al, 2007).…”
Section: Adipogêneseunclassified